GAMBARAN PARENTING STRESS PADA PRIMIPARA : STUDI LITERATURE REVIEW - Milly Maryam Panghela; Muryati Muryati; Nani Avianti; Zaenal Muttaqin (Jurnal Kesehatan Siliwangi, 2020)
Parenting stress is stress as a series of processes that lead to psychological conditions that are not liked and psychological reactions that arise in an effort to adapt to the demands of parental roles. The role of a partner as a parent can be something to be happy but also full of challenges. The challenges in parenting especially new parents or spouses who have just given birth, namely when they become parents will face demands related to the role of care that puts them at risk for experiencing stress. This study aims to determine the description of parenting stress in primiparas. This research method uses descriptive research with the design used is the study of literature. This study uses secondary data obtained not from direct observation but obtained from the results of research conducted by previous researchers. The data collection strategy used in this study is the documentation method in which the researcher draws conclusions and summarizes the literature obtained from search results in accordance with the researcher's topic. Based on the results obtained from 4 literature, it can be concluded that a small proportion of mothers experience high levels of parenting stress, most of the mothers experience parenting stress levels and often occur among mothers, and most mothers experience low level of parenting stress. It is hoped that this literature study can be used as an illustration and reference for nurses as a basis for mental nursing services. Keywords: Parenting Stress, Primipara